(untitled) (European Journal of Formal Sciences and Engineering, 2021)
A great deal of researchers elaborated on the importance of the urban spaces and human life. Urban spaces are necessary types of spaces for a city and they have a timeless value. This research is focused on people’s perception about urban spaces in Larisa, Greece, a medium-sized city selected as case study. An electronic questionnaire survey was conducted and conclusions are drawn on how adequate are the urban spaces in Larisa. Moreover, people are asked to propose ideas on how other spaces, function more as urban gaps, can be integrated on the urban grid. In that way, it is easy to study what people believe about the city’s life and how the existing urban spaces function. Some conclusions derived from this research can be also useful in succeeding a combined traffic and urban planning in other Greek, in the context of the implementation of a Sustainable Urban Mobility Plan (SUMP).